Trends in three malnutrition factors in the global burden of disease: iodine deficiency, vitamin A deficiency, and protein-energy malnutrition (1990–2019) - Ji, Shaorong; Zhou, Yinglu; Zhao, Qilong; Chen, Runtong; Su, Zhenni (Frontiers in Nutrition, 2024)
Background: Vitamin A deficiency, iodine deficiency, and protein-energy malnutrition are prevalent malnutrition issues that disproportionately affect low-income countries and pose significant risks to the health and development of children and adolescents. This study offers a detailed examination of these deficiencies' prevalence trends and gender and regional variations using Global Burden of Disease Study data from 1990 to 2019. It also assesses the specific impact on various age groups, providing essential insights for targeted health interventions and policy-making.Methods: Data spanning from 1990 to 2019 on Vitamin A deficiency, iodine deficiency, and protein-energy malnutrition were extracted from the 2019 Global Burden of Disease Study. Age-Standardized Incidence Rates (ASR) were computed by gender, region, and etiology, utilizing the estimated annual percentage change (EAPC) to assess temporal trends.In 2019, Central Sub-Saharan Africa had the highest prevalence of Vitamin A deficiency, particularly among males, and iodine deficiency peaked in the same region for both genders. South Asia had the highest incidence of protein-energy malnutrition for both genders.Regions with a low Socio-Demographic Index (SDI) showed lower ASR for these deficiencies. Notably, Cameroon, Equatorial Guinea, and Maldives recorded the highest ASR for vitamin A deficiency, iodine deficiency, and protein-energy malnutrition, respectively. The declining ASR trend for vitamin A deficiency, especially among males, suggests effective interventions. East Asia saw a significant increase in iodine deficiency ASR from 1990 to 2019, particularly among women, requiring targeted interventions. The rising ASR of protein-energy malnutrition in several regions, especially among men, raises concerns. Vitamin A deficiency primarily affected children and adolescents, iodine deficiency predominantly impacted adolescents and young adults, and protein-energy malnutrition was chiefly observed among children under 5 years old. These 1 Shaorong Ji et al.